Low-melting-point polyester composite short fiber oiling agent and application thereof

By combining high ethylene oxide addition number fatty alcohol polyoxyethylene ether, low ethylene oxide addition number fatty alcohol polyoxyethylene ether, and antistatic agent, the problem of insufficient oil film strength and wettability of low melting point polyester composite short fiber oil agent was solved, and the stability of the spinning process and the improvement of product quality were achieved.

CN119265755APending Publication Date: 2025-01-07SHANGHAI DUOLUN CHEM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411524971.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing low-melting-point polyester composite staple fiber oils are prone to problems such as fiber fuzz, breakage, and fly waste during use, and the oil film strength and wettability are insufficient.

Method used

An oil formulation consisting of high ethylene oxide addition number fatty alcohol polyoxyethylene ether, low ethylene oxide addition number fatty alcohol polyoxyethylene ether, and an antistatic agent is mixed in a mixing tank and stirred evenly under controlled temperature to form an oil emulsion.

Benefits of technology

It improves the oil film strength and fiber surface wettability of the oiling agent, reduces filament breakage during spinning, and ensures uniform oiling of fibers and smooth production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005108970550000031
    Figure BDA0005108970550000031
  • Figure BDA0005108970550000041
    Figure BDA0005108970550000041
  • Figure BDA0005108970550000051
    Figure BDA0005108970550000051
Patent Text Reader

Abstract

The invention relates to a low-melting-point polyester composite short fiber oil agent and application thereof, mainly solves the problem of low oil film strength of a polyester short fiber oil agent on the surface of a low-melting-point polyester composite short fiber in the prior art, and adopts the technical scheme that the low-melting-point polyester composite short fiber oil agent comprises the following components in parts by weight: 40-80 parts of high ethylene oxide adduct number fatty alcohol-polyoxyethylene ether; 1 to 20 parts of glycol monoalkyl ether; and 5-20 parts of an antistatic agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a low melting point polyester composite staple fiber oil agent and application thereof. Background Art

[0002] Low-melting-point polyester composite staple fiber is a composite fiber formed by melting two different polymers, low-melting-point polyester and conventional polyester, and extruding them from a spinneret. It has skin-core, parallel, sea-island, gear, multi-layer parallel and other arrangements. The melting point of low-melting-point polyester is 110-180°C. The melting point of polyester used to produce low-melting-point staple fibers on the market is mostly around 110°C. Low-melting-point polyester and conventional polyester have good compatibility. At a lower processing temperature, low-melting-point polyester melts, while conventional polyester maintains its original physical structure. Therefore, it plays a bonding role in the fiber web, reducing the use of traditional glue. It has the advantages of high peel strength, low hot melt processing temperature, and fast bonding speed. Therefore, it is widely used in sanitary products, textile products, automotive interiors, household products and other fields, and its proportion in the civilian field is increasing.

[0003] In the production process of conventional polyester staple fibers, the polyester staple spinning oil is evenly spread on the fiber surface, which plays a role in smoothing, antistatic and bundling. Due to the low melting point characteristics of low melting point polyester, the pre-spinning oiling of low melting point polyester composite staple fibers is a post-spinning reflux oil emulsion. Generally, the post-spinning adopts the oil tank immersion and rolling oiling method, and no spray oiling is set. The oil tank temperature is set relatively low, generally 20-60℃, and most chemical fiber plants are at room temperature; the drying temperature does not exceed 70℃. In order to facilitate drying and not affect its adhesion application, the oiling rate should not be too high and controlled at 0.08%-0.15%. At present, the oils commonly used in the market for ordinary polyester staple fibers are mainly alkyl phosphates (potassium salts), compounded with higher fatty acid polyoxyethylene esters, or a small amount of amphoteric surfactants, cationic or weakly cationic surfactants. However, when ordinary polyester staple fiber oils are used as low-melting-point polyester composite staple fiber oils, problems such as fiber lint, frequent breakage, and flying flowers are prone to occur. Therefore, low-melting-point polyester composite staple fibers place higher requirements on oils. Summary of the invention

[0004] One of the technical problems to be solved by the present invention is to provide a low melting point polyester composite staple fiber oil agent having the advantage of high oil film strength.

[0005] To solve one of the above technical problems, the technical solution of the present invention is as follows:

[0006] Low melting point polyester composite staple fiber oil, by weight, including:

[0007] High ethylene oxide addition number fatty alcohol polyoxyethylene ether, 40-80 parts;

[0008] Glycol monoalkyl ether, 1 to 20 parts;

[0009] Antistatic agent, 5 to 20 parts.

[0010] The oil agent of the invention is used as a low-melting-point polyester composite staple fiber oil agent, and has high oil film strength.

[0011] In the above technical solution, the low-melting point polyester composite staple fiber oil agent preferably further includes 5 to 30 parts of low ethylene oxide addition number fatty alcohol polyoxyethylene ether. The use of low ethylene oxide addition number fatty alcohol polyoxyethylene ether improves the wettability of the oil agent on the fiber surface.

[0012] In the above technical solution, the proportion of fatty alcohol polyoxyethylene ether with high ethylene oxide addition number is, for example but not limited to, 45, 50, 55, 60, 65, 70, 75, etc.

[0013] In the above technical scheme, the number of parts of low ethylene oxide addition number fatty alcohol polyoxyethylene ether is, for example but not limited to, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, etc.

[0014] We found that fatty alcohol polyoxyethylene ether with high ethylene oxide addition number and fatty alcohol polyoxyethylene ether with low ethylene oxide addition number have a mutually reinforcing effect in improving the oil film strength of the oil agent.

[0015] In the above technical scheme, the number of parts of glycol monoalkyl ether is, for example but not limited to, 2, 3, 4, 5, 6, 7, 8, 9, 10, 12, 14, 16, 18, etc.

[0016] We found that low ethylene oxide addition number fatty alcohol polyoxyethylene ether and glycol monoalkyl ether can enhance each other in improving the wetting performance of oil on fiber surface.

[0017] In the above technical solution, the number of parts of the antistatic agent is, for example but not limited to, 6, 7, 8, 9, 10, 11, 12, 13, 14, 16, 18, etc.

[0018] In the above technical solution, preferably, the fatty alcohol polyoxyethylene ether with high ethylene oxide addition number conforms to the following formula 1:

[0019]

[0020] Wherein, R1 is a C12-C18 hydrocarbon group, such as but not limited to a C12 hydrocarbon group, a C13 hydrocarbon group, a C14 hydrocarbon group, a C15 hydrocarbon group, a C16 hydrocarbon group, a C17 hydrocarbon group, a C18 hydrocarbon group), preferably an alkyl group, which can be a straight-chain alkyl group or a branched alkyl group, but a primary alkyl group can also be a secondary alkyl group; unless otherwise specified, only for comparison, R1 in the embodiments and comparative examples is a straight-chain primary alkyl group. a is the ethylene oxide addition number, a is 50-100, such as but not limited to, a is 55, 60, 65, 70, 75, 80, 85, 90, 95, etc. For comparison only, the high ethylene oxide addition number fatty alcohol polyoxyethylene ethers used in the embodiments and comparative examples are all products obtained by using C16-18 fatty alcohol as initiator to initiate ethylene oxide polymerization. C16-18 fatty alcohol is a mixture of C16 fatty alcohol and C18 fatty alcohol in any weight ratio, but the weight ratio of C16 fatty alcohol to C18 fatty alcohol in the commonly used C16-18 fatty alcohols on the market is between 1:10 and 10:1. The more common weight ratio of C16 fatty alcohol to C18 fatty alcohol has three specifications, 7:3, 5:5 and 3:7, which is also for comparison only. The C16-18 fatty alcohols in the embodiments and comparative examples of the present invention all adopt a specification of 3:7. In the market, fatty alcohol polyoxyethylene ethers synthesized with C16-18 fatty alcohols as starting agents are usually called Pingpingjia O-series. For example, C16-18 fatty alcohol polyoxyethylene (80) ether is usually called Pingpingjia O-80 in the market, and C16-18 fatty alcohol polyoxyethylene (60) ether is usually called Pingpingjia O-60 in the market.

[0021] In the above technical solution, preferably, the fatty alcohol polyoxyethylene ether with low ethylene oxide addition number conforms to the following formula 2:

[0022]

[0023] Wherein, R2 is a hydrocarbon group of C12 to C18, for example but not limited to a hydrocarbon group of C12, a hydrocarbon group of C13, a hydrocarbon group of C14, a hydrocarbon group of C15, a hydrocarbon group of C16, a hydrocarbon group of C17, and a hydrocarbon group of C18. Preferably, the hydrocarbon group is an alkyl group, which may be a straight-chain alkyl group or a branched alkyl group, and the primary alkyl group may also be a secondary alkyl group. Unless otherwise specified, for comparison only, R2 in the embodiments and comparative examples is a straight-chain primary alkyl group. For comparison purposes, the low ethylene oxide addition number fatty alcohol polyoxyethylene ethers used in the embodiments and comparative examples are all products obtained by initiating ethylene oxide polymerization with C12-14 fatty alcohol as initiator. C12-14 fatty alcohol is a mixture of C12 fatty alcohol and C14 fatty alcohol in any weight ratio, but the weight ratio of C12 fatty alcohol to C14 fatty alcohol in the commonly used C12-14 fatty alcohols on the market is between 1:10 and 10:1, and the more common weight ratio of C12 fatty alcohol to C14 fatty alcohol is 7:3. This specification is also only for comparison purposes. The weight ratio of C12 fatty alcohol to C14 fatty alcohol in the embodiments and comparative examples of the present invention is 7:3. In the market, fatty alcohol polyoxyethylene ethers synthesized with C12-14 fatty alcohols as starting agents are usually referred to as AEO series. For example, C12-14 fatty alcohol polyoxyethylene (3) ether is usually referred to as AEO3 in the market, C12-14 fatty alcohol polyoxyethylene (5) ether is usually referred to as AEO5 in the market, C12-14 fatty alcohol polyoxyethylene (7) ether is usually referred to as AEO7 in the market, and so on.

[0024] b is the number of ethylene oxide additions, b is 3-10, for example but not limited to, b is 4, 5, 6, 7, 8, 9, etc., more preferably b is 3-7.

[0025] In the above technical solution, preferably, the glycol monoalkyl ether conforms to the following formula 3:

[0026]

[0027] Wherein R3 is a C1~C6 hydrocarbon group, for example but not limited to a C1 hydrocarbon group, a C3 hydrocarbon group, a C4 hydrocarbon group, a C5 hydrocarbon group, a C6 hydrocarbon group, preferably an alkyl group, which can be a straight-chain alkyl group or a branched alkyl group, and can be a primary alkyl group or a secondary alkyl group; c is the ethylene oxide addition number, and c is 2-5.

[0028] In the above technical scheme, there is no special requirement for the selection of antistatic agent, and those skilled in the art can make a reasonable choice without creative work. For example, those skilled in the art know that alkyl phosphate potassium salt and alkyl polyoxyethylene ether phosphate potassium salt are often used as antistatic agents, and the antistatic agent of the present invention can therefore be at least one of alkyl phosphate potassium salt and alkyl polyoxyethylene ether phosphate potassium salt. Only for comparison, the antistatic agents in the embodiments of the present invention and the comparison are all produced by Shanghai Duolun Chemical Co., Ltd., with the brand name of antistatic agent AS-2202, the active ingredient is AEO3PK, which is an AEO3PK aqueous emulsion with an effective substance mass content of 25%. AEO3PK is obtained by reacting AEO3 with a phosphating agent and then neutralizing with a potassium hydroxide aqueous solution.

[0029] In the above technical solution, preferably, the oil agent includes water.

[0030] In the above technical solution, some of the components other than water are sometimes not supplied in the form of pure substances, but in the form of effective substances dispersed in solvents. In this case, the measurement of each component in the invention is still carried out in the form of effective substances. For example, the antistatic agent AS-2202, the active ingredient is AEO3PK, which is an aqueous emulsion of AEO3PK, and the mass content of the effective substance is 25%. In this case, the antistatic agent is measured in the form of the effective substance AEO3PK, rather than in the form of AS-2202 commodity.

[0031] In order to facilitate storage and on-site dilution, the water content in the oil is preferably 40-80% by mass, or the mass concentration of the active substance in the oil is 20-60%. For example, but not limited to, the mass concentration of the active substance in the oil is 25%, 35%, 40%, 45%, 50%, 55%, etc.

[0032] In order to facilitate the on-site use of fiber oiling, the oil is in the form of an emulsion, and the mass content of water in the oil emulsion is preferably 95.0-99.9%; or the mass content of the oil effective substance in the oil emulsion is 0.1-5.0%. For example, but not limited to, the mass content of the oil effective substance in the oil emulsion is 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, etc.

[0033] The effective substances in the oil are the general term for all components in the oil other than water.

[0034] The technical key of the oil of the present invention is the selection of the various components in the above oil. According to the understanding of those skilled in the art, the various components required for the oil can be evenly mixed without creative labor.

[0035] For example, but not limited to, the preparation method of the oil agent includes the following steps:

[0036] Add measured water into the mixing kettle and heat it to 40-70°C;

[0037] Start stirring, add fatty alcohol polyoxyethylene ether with high ethylene oxide addition number, antistatic agent, fatty alcohol polyoxyethylene ether with low ethylene oxide addition number, and glycol monoalkyl ether in proportion. Stir evenly at the set temperature, cool to 20-50℃ and discharge.

[0038] The second technical problem to be solved by the present invention is to provide the application of the above-mentioned oil.

[0039] In order to solve the above technical problems, the technical solution of the present invention is: the use of any one of the oil agents described in the technical solutions of one of the above technical problems in the production of low-melting point polyester composite staple fibers.

[0040] The technical key of the present invention is the selection of the oil component. As for the specific process conditions used in the production of low-melting-point polyester composite staple fibers, those skilled in the art can make reasonable choices without having to make creative efforts.

[0041] Just as an example, low-melting-point polyester composite staple fiber is oiled during production, and the post-spinning generally adopts the oil tank dipping and rolling method to oil once. After the polyester raw material is melted, it enters the tunnel through the spinneret for cooling, and is oiled by dipping and rolling in the oil tank. The temperature is generally set at 20-60°C, and most chemical fiber plants are at room temperature. The subsequent processes include stretching, shaping, curling, drying, cutting and packaging. The drying temperature does not exceed 70°C. In order to facilitate drying and not affect the adhesion application of the fiber, the oiling rate should not be too high and should be controlled at 0.08%-0.15%.

[0042] Testing of the oil of the present invention

[0043] 1. Test of oil film strength

[0044] The oil film strength of the finished oil was tested using the GB / T3142-2019 lubricant load capacity determination method (four-ball method), characterized by the maximum no-seizure load Pb, using an MRS-10A four-ball friction tester (manufactured by Jinan Huashi Testing Machine Co., Ltd.) at 25°C and a ball milling speed of 1450r / min for 10s. The larger the maximum no-seizure load Pb, the higher the oil film strength of the oil. The oil used in the test is an oil emulsion with an effective mass concentration of 30%.

[0045] 2. Contact angle test

[0046] 2.1 Fiber samples

[0047] The low melting point polyester composite staple fiber (fineness 4D, length 51mm) of Yangzhou Tianfulong Group Co., Ltd. was first washed with pure water for 4 times, and then ultrasonically cleaned with ethanol for 5 minutes to remove surface dust, grease and other impurities. The fiber was taken out and dried in a blast drying oven at 40°C, and then placed in a constant temperature and humidity box at a temperature of 20°C and a relative humidity of 65%RH for more than 24 hours as a fiber sample.

[0048] 2.2 Test liquid

[0049] The oil agent was prepared into an oil agent water emulsion with a mass concentration of 0.10% of the effective substance as the test liquid.

[0050] 2.3 Test Instruments

[0051] Kruss DSA100 contact angle meter.

[0052] 2.4 Test Method

[0053] A 10pL droplet of oil emulsion was pulsed onto a horizontally stretched single fiber sample fixed on a sample stand. The CCD recorded the entire contact process between the droplet and the fiber sample. The static contact angle of the single fiber was calculated using the angle measurement method. The experimental environment conditions were: temperature (20±2)℃, relative humidity 35%±5%. It was forbidden to use the same fiber for repeated testing during the experiment.

[0054] 2.5. Meaning of contact angle

[0055] When the contact angle is 0°, it indicates that the test liquid completely wets the surface of the fiber sample, and complete wetting is also called spreading; when the contact angle is between 0° and 90°, it indicates that the test liquid is wettable on the surface of the fiber sample, and when the contact angle is greater than 90°, it indicates that the test liquid is not wettable on the surface of the fiber sample; when the contact angle is close to the limit value of 180°, it belongs to the super non-wettable situation, which is the so-called lotus leaf effect.

[0056] The present invention is described in detail below through specific implementation modes and examples. DETAILED DESCRIPTION

[0057] [Example 1]

[0058] 1. Oil formulation with 25% active substance concentration

[0059]

[0060]

[0061] 2. Oil preparation

[0062] (1) Add 270 parts by weight of water into a mixing kettle;

[0063] (2) Start stirring, control the kettle temperature to 60° C., then add 60 parts by weight of Peregal O-80, 20 parts by weight of AEO5, 10 parts by weight of diethylene glycol monomethyl ether and 40 parts by weight of AS-2202;

[0064] (3) Continue stirring at 60°C for 120 minutes;

[0065] (4) Cooling to room temperature and discharging to obtain finished oil product.

[0066] 3. Oil performance test

[0067] After testing, the Pb is 825 Newtons and the contact angle is 23.1°.

[0068] 4. Oiling test in the production workshop of low melting point polyester composite staple fiber

[0069] Heat deionized water to 60°C, add low-melting-point polyester composite staple fiber oil while stirring to form an oil emulsion, cool it for use, maintain 60°C and stir for 60 minutes, and the mass concentration of the effective oil in the oil emulsion is 2.0%. After melt spinning → cooling → oiling (pre-spinning oil tank) → bundling → stretching → shaping → oiling (post-spinning oil tank) → curling → drying → cutting and packaging. The oil tank temperature is set to 30°C, the drying temperature is 65°C, and the fiber oiling rate is controlled to 0.10% by spinning speed and padding. During the spinning process, there are few broken ends of the hair and no white powder phenomenon (domestic ordinary polyester staple fiber oil has this common problem of white powder. The composition of white powder is mainly fiber oligomers, and it also contains a small amount of dust, oil, and water impurities. The reason for the generation is that the oil film strength of the oil agent is low and the wettability is poor, resulting in poor oil film strength and uneven thickness). The low-melting-point polyester composite staple fibers produced by the chemical fiber plant have smooth cleaning, normal cotton mesh and uniform yarn dryness in the subsequent downstream spinning process.

[0070] [Example 2]

[0071] 1. Oil formulation with 25% active substance concentration

[0072]

[0073] 2. Oil preparation

[0074] (1) Add 270 parts by weight of water into a mixing kettle;

[0075] (2) Start stirring, control the kettle temperature to 60° C., then add 60 parts by weight of Perga O-60, 20 parts by weight of AEO5, 10 parts by weight of diethylene glycol monomethyl ether and 40 parts by weight of AS-2202;

[0076] (3) Continue stirring at 60°C for 120 minutes;

[0077] (4) Cooling to room temperature and discharging to obtain finished oil product.

[0078] 3. Oil performance test

[0079] After testing, the Pb is 804 Newtons and the contact angle is 23.3°.

[0080] [Example 3]

[0081] 1. Oil formulation with 25% active substance concentration

[0082]

[0083]

[0084] 2. Oil preparation

[0085] (1) Add 255 parts by weight of water into a mixing kettle;

[0086] (2) Start stirring, control the kettle temperature to 60°C, then add 65 parts by weight of Peregrine O-60,

[0087] 15 parts by weight of AEO7, 5 parts by weight of triethylene glycol mono-n-butyl ether and 60 parts by weight of AS-2202;

[0088] (3) Continue stirring at 60°C for 120 minutes;

[0089] (4) Cooling to room temperature and discharging to obtain finished oil product.

[0090] 3. Oil performance test

[0091] After testing, the Pb is 793 Newtons and the contact angle is 25.6°.

[0092] [Comparative Example 1]

[0093] 1. Oil formulation with 25% active substance concentration

[0094]

[0095]

[0096] 2. Oil preparation

[0097] (1) Add 270 parts by weight of water into a mixing kettle;

[0098] (2) Start stirring, control the kettle temperature to 60° C., and then add 60 parts by weight of PEG3000, 20 parts by weight of AEO5, 10 parts by weight of diethylene glycol monomethyl ether and 40 parts by weight of AS-2202;

[0099] (3) Continue stirring at 60°C for 120 minutes;

[0100] (4) Cooling to room temperature and discharging to obtain finished oil product.

[0101] 3. Oil performance test

[0102] After testing, the Pb is 606 Newtons and the contact angle is 26.4°.

[0103] [Example 4]

[0104] 1. Oil formulation with 25% active substance concentration

[0105]

[0106] 2. Oil preparation

[0107] (1) Add 270 parts by weight of water into a mixing kettle;

[0108] (2) Start stirring, control the kettle temperature to 60° C., then add 80 parts by weight of Perigax O-80, 10 parts by weight of diethylene glycol monomethyl ether and 40 parts by weight of AS-2202;

[0109] (3) Continue stirring at 60°C for 120 minutes;

[0110] (4) Cooling to room temperature and discharging to obtain finished oil product.

[0111] 3. Oil performance test

[0112] After testing, the Pb is 659 Newtons and the contact angle is 60.3°.

[0113] [Comparative Example 2]

[0114] 1. Oil formulation with 25% active substance concentration

[0115]

[0116] 2. Oil preparation

[0117] (1) Add 270 parts by weight of water into a mixing kettle;

[0118] (2) Start stirring, control the kettle temperature to 60° C., and then add 80 parts by weight of AEO5, 10 parts by weight of diethylene glycol monomethyl ether and 40 parts by weight of AS-2202;

[0119] (3) Continue stirring at 60°C for 120 minutes;

[0120] (4) Cooling to room temperature and discharging to obtain finished oil product.

[0121] 3. Oil performance test

[0122] After testing, the Pb is 597 Newtons and the contact angle is 22.5°.

[0123] [Example 5]

[0124] 1. Oil formulation with 25% active substance concentration

[0125]

[0126]

[0127] 2. Oil preparation

[0128] (1) Add 270 parts by weight of water into a mixing kettle;

[0129] (2) Start stirring, control the kettle temperature to 60°C, and then add 60 parts by weight of Perga O-80, 30 parts by weight of AEO5 and 40 parts by weight of AS-2202;

[0130] (3) Continue stirring at 60°C for 120 minutes;

[0131] (4) Cooling to room temperature and discharging to obtain finished oil product.

[0132] 3. Oil performance test

[0133] After testing, the Pb is 789 Newtons and the contact angle is 42.8°.

[0134] [Example 6]

[0135] 1. Oil formulation with 25% active substance concentration

[0136]

[0137] 2. Oil preparation

[0138] (1) Add 270 parts by weight of water into a mixing kettle;

[0139] (2) Start stirring, control the kettle temperature to 60° C., then add 60 parts by weight of Peregal O-80, 30 parts by weight of diethylene glycol monomethyl ether and 40 parts by weight of AS-2202;

[0140] (3) Continue stirring at 60°C for 120 minutes;

[0141] (4) Cooling to room temperature and discharging to obtain finished oil product.

[0142] 3. Oil performance test

[0143] After testing, the Pb is 735 Newtons and the contact angle is 55.9°.

[0144] [Comparative Example 3]

[0145] The common polyester staple fiber hair-type oil WY-203 / WY-207D-6 produced by Shanghai Duolun Chemical Co., Ltd. was used for comparison, wherein the WY-203 anionic surfactant compound system has an effective mass content of 35%; the WY-207D-6 nonionic surfactant compound system has an effective mass content of 33%. The proportion of common polyester staple fiber (by effective mass) is WY-203:WY-207D-6=7:3, and the following comparative examples are all prepared according to this ratio to prepare the oil emulsion.

[0146] 1. Oil formulation with 25% active substance concentration

[0147] According to the conventional weight ratio of WY-203 and WY-207D-6 for ordinary polyester staple oil, that is:

[0148] WY-203 (active substance concentration 35.0%), 100 parts by weight;

[0149] WY-207D-6 (active substance concentration 33.0%), 45 parts by weight;

[0150] Water, 54 parts by weight.

[0151] 2. Oil preparation

[0152] (1) Add 54 parts by weight of water into the mixing kettle.

[0153] (2) Start stirring, heat to 60°C, then add 100 parts by weight of WY-203 and 45 parts by weight of WY-207D-6;

[0154] (3) Control the kettle temperature to 60°C and continue stirring for 120 minutes;

[0155] (4) Cool to room temperature and set aside.

[0156] 3. Oil performance test

[0157] After testing, the Pb is 642 Newtons and the contact angle is 27.9°.

[0158] 4. Oiling test in the production workshop of low melting point polyester composite staple fiber

[0159] Heat deionized water to 60°C, add ordinary polyester staple fiber oil while stirring to make an oil emulsion, cool it for use, maintain 60°C and stir for 60 minutes, the mass concentration of the oil emulsion is 2.0%. After melt spinning → cooling → oiling (pre-spinning oil tank) → bundling → stretching → shaping → oiling (post-spinning oil tank) → curling → drying → cutting and packaging. The oil tank temperature is set to 30°C, the drying temperature is 65°C, and the oiling rate of the fiber is controlled to 0.10% by spinning speed and padding. During the spinning process, the hair fibers are often broken and a slight white powder appears.

Claims

1. Low melting point polyester composite staple fiber oil, by weight, including: High ethylene oxide addition number fatty alcohol polyoxyethylene ether, 40-80 parts; Glycol monoalkyl ether, 1 to 20 parts; Antistatic agent, 5-20 parts; Preferably, the invention further comprises 5 to 30 parts of fatty alcohol polyoxyethylene ether with low ethylene oxide addition number.

2. The oil according to claim 1, characterized in that The fatty alcohol polyoxyethylene ether with high ethylene oxide addition number conforms to the following formula 1: Wherein, R1 is a C12-C18 hydrocarbon group. a is the number of ethylene oxide additions, and a is 50-100.

3. The oil according to claim 1, characterized in that The low ethylene oxide addition number fatty alcohol polyoxyethylene ether conforms to the following formula 2: Wherein, R2 is a C12-C18 hydrocarbon group; b is the number of ethylene oxide additions, and b is 3-10.

4. The oil according to claim 3, characterized in that b is 3 to 7.

5. The oil according to claim 1, characterized in that The glycol monoalkyl ether conforms to the following formula 3: Wherein R3 is a C1~C6 hydrocarbon group. c is the number of ethylene oxide additions, and c is 2-5.

6. The oil according to claim 1, characterized in that The antistatic agent is at least one of alkyl phosphate potassium salt and alkyl polyoxyethylene ether phosphate potassium salt.

7. The oil according to claim 1, characterized in that The oil agent includes water.

8. The oil according to claim 7, characterized in that the mass content of water in the oil is 40-80%; or the mass concentration of the effective substance in the oil is 20-60%.

9. The oil according to claim 7, characterized in that The mass content of water in the oil emulsion which is convenient for direct use at the use site is 95.0-99.9%, or the mass content of the oil effective substance in the oil emulsion is 0.1-5.0%.

10. Use of the oil according to any one of claims 1 to 9 in the production of low-melting-point polyester composite staple fibers.